Vitamin D Deficiency in a Pediatric Population with Sickle Cell Disease - De Moraes-Ferrari, G (Taylor and Francis Ltd., 2025)
Pediatric patients with sickle cell disease and vitamin D deficiency have worse clinical and laboratory outcomes. This study aims to quantify the prevalence of vitamin D deficiency in this population and identify possible risk factors for hypovitaminosis D by performing a cross-sectional study with children aged 3–18 years old with sickle cell disease. Sixty patients were evaluated, with a mean age of 10.80 + 4.21 years. The prevalence of vitamin D deficiency was 46.7% (21.02 ± 8.47 ng/mL). Patients were clustered into two groups regarding vitamin D deficiency (25-OH-D < 20 ng/mL). When comparing groups with and without vitamin D deficiency, age (p = 0.002) and season of 25-OH-D collection (p = 0.005) were statistically significant. Age presented OR 1.23 (95% CI: 1.07; 1.41/p = 0.004), as well as the season of the 25-OH-D collection with OR 5.21 (95% CI: 1.58; 17.14/p = 0.007) for autumn/winter assessment. After linear regression, an association was noted for age (β = −0.80/95% CI: −1.29; −0.320/p = 0.002), days of sun exposure (β = 0.83/95% CI: 0.07; 1.58/p = 0.032), and autumn/winter vitamin D assessment (β = −7.94/95% CI: −12.02; −3.85/p = 0.032). In conclusion, hypovitaminosis D is highly prevalent in this population; meanwhile, age, season of 25-OH-D collection, and days of sunlight exposure appeared as risk factors for deficiency. © 2025 Taylor & Francis Group, LLC.